Economic Growth and Renewable and Non-renewable Energy Consumption: Evidence From the U.S. States - Salari, Mahmoud (Archīum Ateneo, 2021)
Energy consumption and economic growth play an important role in the global policy debate among policymakers around the world. This is the first study to investigate the relationship between economic growth and energy consumption at the state level for the U.S. from 2000 to 2016. As opposed to country-level studies, a focus on states within a country allows for comparisons across more homogeneous entities. The four known hypotheses are tested: growth, conservative, feedback, and neutral, differentiating between renewable and non-renewable energy consumption. In order to address endogeneity, two strategies are developed: (1) a static analysis for 2016 where key policy covariates are gradually added to the model, and (2) a dynamic analysis using different generalized method of moments (GMM) estimators. The model is augmented using socioeconomic, regulatory and climatic variables, which allows for the evaluation of policies while facilitating a transition to renewable energy use. Overall, the results show that total energy consumption and non-renewable energy consumption support the feedback hypothesis. Results for renewable energy, industrial energy, and residential energy consumption show more support for the growth hypothesis. These results have policy implications in terms of optimizing decisions and investments to efficiently improve economic growth while reducing energy consumption.